Mapping Degas : real spaces, symbolic spaces and invented spaces in the life and work of Edgar Degas (1834-1917) /: real spaces, symbolic spaces and invented spaces in the life and work of Edgar Degas (1834-1917). (2015) - Crisci-Richardson, Roberta
No abstract available